Effect of Health Education on Postpartum Mothers’ Knowledge of Colostrum in Bantaeng, Indonesia - Kartini, Anita; Sumarmi, Sumarmi; Sri Kurnia Sah Puteri; Nurul Zaskia (Omni Nursing Journal, 2025)
Background: Exclusive breastfeeding is a global initiative to ensure healthy growth from an early age. Colostrum, the first breast milk, provides essential nutrients and immunity support, in line with the Sustainable Development Goals (SDGs) 2030. Objective: To describe the knowledge of postpartum mothers about colostrum before and after health education. Methods: This study used a pretest–posttest design without a control group. Results: Before the intervention, 5 respondents (16.6%) had good knowledge, while 16 respondents (53.4%) had poor knowledge. After health education, 17 respondents (56.6%) demonstrated good knowledge, and only 3 respondents (10.1%) remained in the poor knowledge category. Conclusion: Health education significantly improved postpartum mothers’ knowledge about colostrum.